2022
DOI: 10.1021/acsomega.2c05298
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Perfluoropolymers on the Anti-Wear Properties of Carbon Fiber/Polyphenylene Sulfide Composites: A Comparative Study

Abstract: In this work, several perfluoropolymers (PFP), including commercial polytetrafluoroethylene (PTFE), perfluorinated ethylene–propylene copolymer (FEP), tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA), and irradiated PTFE (iPTFE) were used as additives to lubricate carbon fiber (CF)-reinforced polyphenylene sulfide (PPS) composites. The tribological properties of the yielding composites were studied and correlated with the melt processability of PFPs. Although the neat FEP and PFA have higher fric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…A comparison of both average μ and w for PPS‐based composites between this work and literature was displayed in Figure 4. The results indicated that PPS/i‐PTFE20 performed better when compared with the reported literature, which suggests that the use of irradiation treated PTFE powders was instrumental in improving the tribological performance of PPS‐based composites 18,19,21,22,50–56 …”
Section: Resultsmentioning
confidence: 75%
See 3 more Smart Citations
“…A comparison of both average μ and w for PPS‐based composites between this work and literature was displayed in Figure 4. The results indicated that PPS/i‐PTFE20 performed better when compared with the reported literature, which suggests that the use of irradiation treated PTFE powders was instrumental in improving the tribological performance of PPS‐based composites 18,19,21,22,50–56 …”
Section: Resultsmentioning
confidence: 75%
“…The EDS elemental analysis of the transfer film was depicted in Figure 8f and corresponding results were tabulated in Table 2. It was clear that there was a higher fraction of C and O on the sliding counterpart of PPS, which was likely related to the fact that severer tribo‐oxidation reaction occurred at the sliding interface 55 . Moreover, the content of F element on the surface of the sliding counterpart of PPS/i‐PTFE20 was 3.72%, which was a result of the formation of transfer film due to the adherence of i‐PTFE molecular chains to the friction pair.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations